2021
DOI: 10.2147/jir.s304828
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Plant gma-miR-159a, Identified by miRNA Library Functional Screening, Ameliorated Hepatic Stellate Cell Activation and Inflammation via Inhibiting GSK-3β-Mediated Pathways

Abstract: Plant-derived exogenous microRNAs (miRNAs) regulate human physiological functions by blocking the translation of target mRNAs. Although several computational approaches have been developed to elucidate the interactions of cross-species miRNAs and their targets in mammals, the number of verified plant miRNAs is still limited, and the biological roles of most exogenous plant miRNAs remain unknown. Methods: A miRNA mimic library-based phenotypic screening, which contained 8394 plant mature miRNAs published in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…In this study, xeno-miRNAs were detected in the blood and milk of both high-fat-milk and low-fat-milk dairy cows, which demonstrated that xeno-miRNAs could be absorbed into the tissues of dairy cows. This was consistent with previous studies that demonstrated direct uptake of plant miRNAs into animals without special treatment [ 4 , 10 , 27 , 28 , 29 ]. The expression levels of xeno-miRNAs in blood and milk were statistically different in dairy cows within the same group (high-fat group or low-fat group), which might have been related to their variable intake and/or metabolic traits of individual dairy cows.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, xeno-miRNAs were detected in the blood and milk of both high-fat-milk and low-fat-milk dairy cows, which demonstrated that xeno-miRNAs could be absorbed into the tissues of dairy cows. This was consistent with previous studies that demonstrated direct uptake of plant miRNAs into animals without special treatment [ 4 , 10 , 27 , 28 , 29 ]. The expression levels of xeno-miRNAs in blood and milk were statistically different in dairy cows within the same group (high-fat group or low-fat group), which might have been related to their variable intake and/or metabolic traits of individual dairy cows.…”
Section: Discussionsupporting
confidence: 93%
“…There are several classic examples of cross-kingdom regulation by miRNAs. For example, miR159a from soybean can inhibit NF-κB and TGF-β1 signaling in mice, which helps prevent hepatic fibrosis [ 3 , 4 ]. Another notable example is the ability of miR2911 in the decoction of honeysuckle to inhibit the replication of the influenza A virus, and it could also inhibit SARS-CoV-2 replication and accelerate the negative conversion of infected patients [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…When exogenous miRNAs enter the human body, they seem to act similarly to endogenous miRNAs, participating in the host body’s management of life activities. By suppressing GSK3β-mediated NF-κB and transforming growth factor beta 1 (TGF-β1) pathways, soybean-derived gma-miR159a improves hepatic stellate cell activation and lowers inflammation (Yu et al 2021 ). Moreover, cross-kingdom gene regulation by miRNAs has initiated the hot topic of the potential function of miRNAs on human or mice gene expression after oral administration.…”
Section: The Role Of Exogenous Mirnasmentioning
confidence: 99%
“…Such miRNAs include miR-124a, which can directly target MCP-1 mRNA; miR-21, miR-let7, miR-146a, miR-146b, miR-126, miR-155, and miR-199a, which intervene with the downstream inflammatory mediators of TLR, IL-1, and NF-κB. , However, Rai et al found that miR-155 can promote B cell lymphoma, which has been correlated with milk consumption . In addition, Yu et al reported that plant gma-miR-159a effectively alleviated liver inflammation in TGF-β1- and PDGF-induced hepatic stellate cell (HSC)- and CCl 4 -induced hepatic fibrosis mouse models, primarily through inhibiting the GSK-3β-mediated NF-κB and TGF-β1 pathways. Xu et al researched the effect of orally administered oat-derived ELNs (O-ELNs) on alcohol-induced brain inflammation.…”
Section: Anti-inflammatory Actionsmentioning
confidence: 99%
“…61,62 However, Rai et al 63 found that miR-155 can promote B cell lymphoma, which has been correlated with milk consumption. 64 In addition, Yu et al 65 reported that plant gma-miR-159a effectively alleviated liver inflammation in TGF-β1and PDGF-induced hepatic stellate cell (HSC)-and CCl 4induced hepatic fibrosis mouse models, primarily through inhibiting the GSK-3β-mediated NF-κB and TGF-β1 pathways. Xu et al 66 the induction of multiple diseases, such as Alzheimer's and type 2 diabetes.…”
Section: ■ Anti-inflammatory Actionsmentioning
confidence: 99%